Controversies of Javanese Style Murattal among Nahdlatul Ulama Figures - Imam Muhsin; Moch. Wasil (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2024)
This study aims to compare perspectives on Javanese-style murottal among Nahdlatul Ulama (NU) figures. NU, with its strong cultural roots, tends to adopt the Javanese style in its engagement with the Quran, viewing it as an infrastructure that can be integrated with local values. However, NU figures have differing perspectives on the phenomenon of combining the Javanese style with Quranic recitation. This study involves content analysis and literature review, as well as the examination of lectures on social media to understand their approach to the Quran in the Javanese cultural context. The results of this study can provide a more comprehensive understanding of the characteristics of Islamic thought in Indonesia, particularly in addressing the Javanese-style murottal from the perspective of NU figures. Thus, this study aims to offer deeper insights into the diversity of Islamic understanding within the Javanese cultural context in Indonesia.